Analisis Efektivitas Proses Pembuatan Paspor di Kantor Imigrasi Kelas I Tanjungpinang - Nisrina Qanitah (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
The analysis of the effectiveness of the passport service process at the Tanjungpinang Class I Immigration Office aims to assess the quality of service to passport applicants. This study identifies various factors that affect the effectiveness of the process, such as process speed, demand satisfaction, and the use of information technology. The method used in this study is a qualitative approach through data collection conducted through literature studies. From the results of the analysis, although the Tanjungpinang Class I Immigration Office has implemented an organized queuing system, there are still several things that hinder the passport making process such as the inadequate number of officers and limited facilities. In addition, the level of complaint satisfaction also varies because there are complaints complaining about long waiting times and lack of information about procedures, while on the other hand, they can access services through online registration and the ease of information technology in doing various things. This study recommends improving personnel services, training in improving customer service, and developing a more efficient information system to speed up the passport making process. Thus, the services of the Tanjungpinang Class I Immigration Office will be more effective according to public expectations.